2018
DOI: 10.1016/j.scitotenv.2018.04.392
|View full text |Cite
|
Sign up to set email alerts
|

How informative is the response of Ground Beetles' (Coleoptera: Carabidae) assemblages to anthropogenic land use changes? Insights for ecological status assessments from a case study in the Neotropics

Abstract: Ground Beetles (Carabidae) have been suggested to be used as indicators of ecological status under the effects of anthropogenic land use and land cover changes in highly biodiverse regions such as the Neotropics. In this study Ground Beetles' assemblages from a region in the Brazilian Amazon were investigated for evaluating their applicability as disturbance indicators. Differences in assemblages between ecosystems, discriminated by complimentary methodologies, demonstrate a sensitive reaction from the most pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 76 publications
(95 reference statements)
1
15
1
3
Order By: Relevance
“…Contrary to our results, previous studies have shown that pristine vegetation support greater arthropod richness and abundance than disturbed areas (Cajaiba et al, ; Mauda et al, ; Van Nuland & Whitlow, ). In our study, species richness and abundance of all arthropod guilds were not influenced by any of the measured factors (rockiness, disturbance and the interaction between these factors).…”
Section: Resultscontrasting
confidence: 99%
“…Contrary to our results, previous studies have shown that pristine vegetation support greater arthropod richness and abundance than disturbed areas (Cajaiba et al, ; Mauda et al, ; Van Nuland & Whitlow, ). In our study, species richness and abundance of all arthropod guilds were not influenced by any of the measured factors (rockiness, disturbance and the interaction between these factors).…”
Section: Resultscontrasting
confidence: 99%
“…Our results support the applicability of SDB metrics as ecological indicators for the management of forests in the region under study, demonstrating that several forest-dependent species could disappear if the forests are replaced by an agricultural landscape (e.g. Pa or Ag) (Cajaiba et al, 2018).…”
Section: Neotropical Small Dung Beetles Assemblages' Composition As Isupporting
confidence: 79%
“…Most studies evaluate impacts of anthropogenic landscape change on biodiversity trends and ecosystem functioning via diverse indexes derived from taxonomic information (Barragán et al, ; Cajaiba, Périco, Caron, et al, ; Cajaiba, Périco, da Silva, Vieira, et al, ; Verdu et al, ). Comparing and complementing taxonomically derived indicators with functional indicators enable linking biodiversity changes with functional changes, in our study through the interplay between GDB taxonomic diversity and GDB trait combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen environmental variables, considered with potential influence on GDB communities and ecosystem functioning, were measured in the sampled ecosystems (Cajaiba et al, ): temperature (T), humidity (H), precipitation (P), circumference at breast height (CBH), circumference at ankle height (CAH), canopy cover (CC), richness of plants (RP), abundance of plants (AP), richness of shrubs (RS), abundance of shrubs (AS), percentage of exposed soil (PES), percentage of green (vegetation) cover (GC), percentages of leaf litter cover (LLC), height of leaf litter (HLL). Information concerning the methodology associated with each variable monitoring is depicted in Table S2, Supplementary material.…”
Section: Methodsmentioning
confidence: 99%